Modifikasi Blower Pembantu Pengeluaran Dedak Pada Mesin Pemutih Beras (Rice Polisher) - Ganda Guna Ngumbara; Andriyono Andriyono; Yosefina Mangera (AGRICOLA, 2018)
The purpose of this research is to design the auxiliary blower that can be used to overcome theblockage on the bran expenditure correct and to know the speed of the blower. The method of thisresearch consisted of the first step (literature study, proposal masking, equipment and material supplyand design the auxiliary blower tool), the second stage is the making of bran blower auxiliary tool, andthird step is the test (measuring wind speed in the blower using anemometer, comparing the level ofcleanliness of rice from rice bran, and recapitulation of tool making). The results obtained in the fieldconditions 3.5-inch pulley of 16.6 m/s has a moderate wind speed so that groats are not much wasted.The percentage of whole rice after using the blower on the second observation that is using the 2.5-inch pulley of 98.12%, the third using 3.5-inch pulleys of 97.56%, the fourth using 4.5-inch pulleys of95.70% and treatment before using blower 89.59%. Based on the recapitulation of the tool making, thetotal cost of making the tool are Rp.2.505.500.